Cannabis cultivation within a religious context: A case study of Ghomara in the Rif Mountain (Northern Morocco). Issue 1 (2nd January 2019) - Yassin, Meklach; Haluza-Delay, Randolph; Kadiri, Mohamed; Ouahrani, Abdeltif El; Mesa, Joaquin Molero; Merzouki, Abderrahmane
ABSTRACT: To understand the relationship between Muslim religious attitudes and the growing/consumption of cannabis, we surveyed 251 residents and conducted interviews in Northern Morocco. The local population is Ghomarian, an ethnic group of Berber heritage that experienced socioeconomic marginalization. Cannabis is grown throughout the region, despite Islamic legal code (shari'a) that makes cannabis, like any substances that alter consciousness, illicit (haram). The survey aimed to gather (a) the perceptions of the local population toward the cultivation of cannabis and its consumption and (b) their attitudes and intention to abandon or to continue this activity despite its unlawful aspect under Islamic legislation (Shari'a). Qualitative interviews provide additional understanding of the rationales of people in the region about cannabis cultivation in the context of religion. The investigation revealed the complexity of how religious beliefs, socioeconomic marginalization, and immoral/illegal economic practices overlap and coexist in Ghomara Region (or in Northern Morocco).